Efficacy and safety of photobiomodulation combined with oral cryotherapy on oral mucosa pain in patients with burning mouth syndrome: a multi-institutional, randomized, controlled trial - Chenghui Lu; Xuan Zhou; Chenglong Yang; Xinxiang Jiang; Xin Li; Zefan Huang; Qing Du; Guoyao Tang (BMC Medicine)
Abstract Background The prevalence of burning mouth syndrome (BMS) is approximately 8% in clinical patients; thus, BMS remains a therapeutic challenge. Photobiomodulation (PBM) and oral cryotherapy (OCT) have been evaluated for the treatment of burning pain, but no confirmatory trials have been performed. To evaluate the comparative effectiveness of PBM combined with OCT at reducing pain and psychological distress compared with PBM alone, OCT alone, or drug therapy (DT) alone in a cohort of patients with BMS. Methods This multi-institutional, single-blinded (assessor-blinded), randomized controlled trial with 4 treatment groups was conducted at Xinhua Hospital, Shanghai Jiao Tong University School of Medicine and Affiliated Stomatology Hospital of Guilin Medical University from December 12, 2022, to January 24, 2024. Among the 156 patients assessed for eligibility, 28 were excluded, and 128 patients with a BMS qualified for randomization to 1 of the 4 treatment groups. The participants received 7 treatment sessions of (1) PBM combined with OCT, (2) PBM, (3) OCT, or (4) DT during a 7-week period. The coprimary outcome measures were changes in visual analogue scale (VAS) scores and the overall response rate between baseline and 7 weeks of treatment. Results After 7 weeks of treatment, the PBM + OCT group achieved a high overall response rate for pain reduction (81.25%). This difference in pain reduction trends between the groups resulted in a nearly fivefold greater mean change in the VAS score at the 12-week assessment for the PBM + OCT group than for the DT group (p < 0.0083). Furthermore, anxiety symptoms were also significantly alleviated by PBM combined with OCT, resulting in a nearly tenfold greater mean change in the GAD-7 score at the 7-week assessment in the PBM + OCT group than in the DT group (p < 0.0083). No severe adverse events were reported during the study period. Conclusions PBM and OCT combination therapy reduces oral mucosa pain and alleviates anxiety symptoms in patients with BMS; thus, this combination therapy is expected to become a promising pain management option for patients with BMS. Trial registration Chinese Clinical Trial Registry Identifier: ChiCTR2300074518.